Dynamical Characteristics of Electromechanical Energy Dissipation due to Translatory Motion: A Minimal Example. Issue 1 (18th November 2019) - Boy, Felix; Hetzler, Hartmut; Tchomgue Simeu, Arnold
Abstract: Electromechanical systems cover a broad technological range of application. Typical examples are electrical machines, eddy current brakes, or different types of actors and sensors. Their dynamical behaviour is affected by some challenging peculiarities: among those are strong geometrical and physical non‐linearities. Consequently, all these effects may result in different kinds of vibration issues. Within this contribution, the classical textbook example of a simple mechanical oscillator is coupled with a magnetic and an electrical circuit. The dynamical characteristics of this system are discussed with respect to equilibria and stationary solutions. Non‐linear periodic solutions are approximated using the harmonic‐balance method.